2020
DOI: 10.1111/mmi.14572
|View full text |Cite
|
Sign up to set email alerts
|

Single‐molecule tracking reveals that the nucleoid‐associated protein HU plays a dual role in maintaining proper nucleoid volume through differential interactions with chromosomal DNA

Abstract: HU (Histone‐like protein from Escherichia coli strain U93) is the most conserved nucleoid‐associated protein in eubacteria, but how it impacts global chromosome organization is poorly understood. Using single‐molecule tracking, we demonstrate that HU exhibits nonspecific, weak, and transitory interactions with the chromosomal DNA. These interactions are largely mediated by three conserved, surface‐exposed lysine residues (triK), which were previously shown to be responsible for nonspecific binding to DNA. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(51 citation statements)
references
References 68 publications
10
40
1
Order By: Relevance
“…We observed cooperative binding of wild-type HUα 2 to both the linear duplex and cruciform DNA in solution with similar calculated Hill coefficients ( h ) and dissociation constants ( K d ) (non-specific binding: h = 3.2 and K d = 0.101 µM; structure-specific binding: h = 2.8 and K d = 0.096 µM) (Figure 1). However, the linear duplex did not migrate as discrete retarded species in EMSA, consistent with weak and transitory non-specific binding (Bettridge et al, 2020; Pinson et al, 1999), but the cruciform DNA migrated as four discrete bands, indicative of strong, cooperative binding of each cruciform DNA molecule to four molecules of HUα 2 as suggested previously (Bonnefoy et al, 1994). The P63A mutation reduced the cooperative binding to cruciform DNA with K d = 0.149 µM, h =1.6, validating the importance of P63 in binding to a distorted DNA as suggested by crystal structures of HU-structure-specific DNA complexes (Guo and Adhya, 2007; Swinger et al, 2003), but it did not affect the binding to the linear DNA duplex ( K d 0.106 µM, h = 3.0).…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…We observed cooperative binding of wild-type HUα 2 to both the linear duplex and cruciform DNA in solution with similar calculated Hill coefficients ( h ) and dissociation constants ( K d ) (non-specific binding: h = 3.2 and K d = 0.101 µM; structure-specific binding: h = 2.8 and K d = 0.096 µM) (Figure 1). However, the linear duplex did not migrate as discrete retarded species in EMSA, consistent with weak and transitory non-specific binding (Bettridge et al, 2020; Pinson et al, 1999), but the cruciform DNA migrated as four discrete bands, indicative of strong, cooperative binding of each cruciform DNA molecule to four molecules of HUα 2 as suggested previously (Bonnefoy et al, 1994). The P63A mutation reduced the cooperative binding to cruciform DNA with K d = 0.149 µM, h =1.6, validating the importance of P63 in binding to a distorted DNA as suggested by crystal structures of HU-structure-specific DNA complexes (Guo and Adhya, 2007; Swinger et al, 2003), but it did not affect the binding to the linear DNA duplex ( K d 0.106 µM, h = 3.0).…”
Section: Resultssupporting
confidence: 82%
“…Here the HU structure-specific binding indirectly impacts the chromosome partitioning through alteration of gene expression. We found that only the non-specific binding participated in a major role of HU - its association with the chromosomal DNA that dictates the chromosome structure and organization. By tracking single molecule analysis in live cells, we have previously demonstrated (Bettridge et al, 2020) and further confirmed here that the non-specific binding of HU is responsible for this interaction with rapid association and dissociation kinetics that keep most HU within the nucleoid. Mutating the three lysine residues to alanine dramatically altered the interacting dynamics of HUα 2 but mutating P63 to alanine did not have any effect (Bettridge et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations